Theological Education in a New Missional Era: A Personal Journey with Seven Theses. (December 2014) - Rooms, Nigel
Abstract The author's personal journey in discovering, developing, researching and practicing adult theological education in the church is rehearsed, pointing out key learning moments along the way. Out of this praxis seven theses are offered that set an agenda for theological education in the new missional era in which the church finds itself.